Using HET taxonomy to help stop human error - Li, Wen-Chin; Harris, Don; Stanton, Neville A.; Hsu, Yueh-Ling; Chang, Danny; Wang, Thomas; Young, Hong-Tsu (Cranfield University, 2010)
Flight crews make positive contributions to the safety of aviation operations. Pilots have to assess continuously changing situations, evaluate potential risks, and make quick decisions. However, even well-trained and experienced pilots make errors. Accident investigations have identified that pilots’ performance is influenced significantly by the design of the flightdeck interface. This research applies hierarchical task analysis (HTA) and utilizes the Human Error Template (HET) taxonomy to collect error data from pilots during flight operations when performing a go-around in a large commercial transport aircraft.
Keywords: Aviation Safety, Cockpit Design, Hierarchical Task Analysis, Human Error Template